Risk Factors for Anterior Cruciate Ligament Injury: literature Review - Mansi, Suleiman Ali (Journal of medical and pharmaceutical sciences, 2019)
The Anterior cruciate ligament (ACL) plays an important role in maintaining knee-joint stability. Most ACL injures (approximately 65%) are due to a non-contact mechanism during physical activities, particularly in sports involving a landing from a jump, pivoting on the leg, rapid deceleration and cutting maneuvers. The average injury of ACL rates is still high for both professional and recreational athletes in particular between the group ages of 15 to 25 year old. The purpose of this article was to review and analysis the causes and potential risk factors for the ACL injury. Several anatomic and neuromuscular risk factors are associated with increased risk of suffering ACL injury, such as shoe-surface interaction, quadriceps angle, knee-joint laxity, genu varum of knee, and body composition. These risk factors most likely act in combination to influence the risk of ACL injury. Therefore, these factors should be considered when designing training programs, competitions, and implementing ACL injury prevention programs.